*

( n1 | u1 n2 | u2 -- n3 | u3 )

Multiply n1 | u1 by n2 | u2 giving the product n3 | u3.

Testing:

T{  0  0 * ->  0 }T          \ TEST IDENTITIE\S
T{  0  1 * ->  0 }T
T{  1  0 * ->  0 }T
T{  1  2 * ->  2 }T
T{  2  1 * ->  2 }T
T{  3  3 * ->  9 }T
T{ -3  3 * -> -9 }T
T{  3 -3 * -> -9 }T
T{ -3 -3 * ->  9 }T

T{ MID-UINT+1 1 RSHIFT 2 *               -> MID-UINT+1 }T
T{ MID-UINT+1 2 RSHIFT 4 *               -> MID-UINT+1 }T
T{ MID-UINT+1 1 RSHIFT MID-UINT+1 OR 2 * -> MID-UINT+1 }T

ContributeContributions